Pengaruh Islamic Branding Dan Customer Religiosity Terhadap Keputusan Pembelian Produk Pada Minimarket Al-Khaibar - Milhan Nur Kholiq; Jeni Susyanti; Arini Fitria Mustapita (E-JRM : Elektronik Jurnal Riset Manajemen, 2022)
Abstract The number of businesses in the retail sector at this time makes entrepreneurs to implement better marketing strategies, not only preparing accurate marketing strategies but also need to provide brands that are suitable for the characteristics of consumers, such as the Al-Khaibar minimarket which uses Islamic branding as an identity. in providing or offering products that are in accordance with consumer needs. Seeing Indonesia as a Muslim country with the highest population level makes this a very good marketing strategy.In this study using a quantitative approach with primary data. This research was conducted by distributing questionnaires to consumers of the Al-Khaibar minimarket. The total sample in this study was 95 respondents and then processed using SPSS statistical software and then using multiple linear regression. The analysis used in this study included measurements of validity and reliability tests as well as classical assumptions.The findings in this study indicate that Islamic branding and religiosity have a significant influence on purchasing decisions, both simultaneously and partially. So it can be concluded that the stronger the Islamic branding created and the higher the level of buyer religiosity, the purchasing decisions will also increase. Keywords: Islamic branding, Religiossty, Purchasing decision.